A MINIMAL INVASIVE TECHNIQUE FOR A LONG TRANS-SPHINCTERIC FISTULA IN ANO- A CASE STUDY - Kumar Shil, *Aditya; Sahu, Priyanka; Kumar, P. Hemantha (International Journal of Ayurveda and Pharma Research, 2017)
Fistula in ano is an uncommon condition of the GIT, with a prevalence of 0.01% in the general population, with higher frequency in men than in women at 2:1 ratio. Complete fistulotomy is the current surgical procedure opted by many surgeons but it may concedes potential complications such as displacement of the anal canal, incontinence, uneven gluteal contour with ugly scar and high rate of recurrence. Presentation of case: Study was conducted on a male patient aged 28 years, with non-healing wound on left gluteal region since eight months pain and swelling in perianal region since two days, on per rectal examination internal opening was found on 6 o clock and external opening at 4 o clock approx.6 inches from the anal verge, diagnosed as trans-sphincteric fistula in ano. In this case study we applied a technique to save the tissue and low complications. We applied two Ksharsutra, one for cutting the tract and second for drainage was used. Second Ksharsutra removed within 2 week after proper drainage. After 6 Ksharsutra change cut through was done at 6 o clock position .wound was healed after six weeks. Conclusion: Fistula in ano having distant external opening such as in gluteal region is rare condition. The present study involved a minimal invasive technique which has negligible complications with a sure cure.